Kaji Eksperimen Output Energi Termoelektrik TEG-SP1848-27145SA Dengan Sumber Panas Dari Solar Parabolic Trough - Muhammad Taufiqurrahman; Gita Suryani Lubis; Muhammad Ivanto; Putro Setio (Proklamasi 45 University, 2022)
Solar energy is the energy that is most easily obtained in the conditions of our country which is in an area that is crossed by the equator. Energy that can be in the form of sunlight and heat from the sun can certainly be used as alternative energy to produce electrical energy. One technology that is able to utilize solar thermal energy is a solar parabolic trough system as a solar thermal collector. From the heat source produced, it is expected to be able to produce electrical energy generated by thermoelectric, where the thermoelectric heat side is obtained from the heat source in the solar parabolic trough. By conducting experiments to manufacture a power plant that utilizes a solar parabolic trough which is integrated with a thermoelectric type TEG-SP1848-27145SA as many as seven pieces, then the experimental data is taken from the device capable of producing electrical energy output. The output of electrical energy in the form of electrical voltage produced is strongly influenced by the difference in temperature on the hot and cold side of the thermoelectric, the greater the temperature difference, the greater the energy output that can be generated. From the experimental results, the highest temperature difference produced is 20.7oC with a current value of 85.93 mA and a voltage of 2.51 volts in the direction facing north, and the highest temperature difference produced is 11.5oC with a current value of 77.63 mA and a voltage of 2.15 volts in the direction facing east to west. The highest thermoelectric efficiency is 14.996% with the direction of the solar parabolic trough facing east to west.